State of the World's Cities 2008/2009 harmonious cities - UN Habitat (London Earthscan, 2008)
This report adopts the concept of Harmonious Cities as theoretical framework in order to understand today's urban world, and also as an operational tool to confront the most important challenges facing urban areas and their development processes. It recognises that tolerance, diversity, social jstice and good governance, all of which are inter-related, are as important to sustainable urban development as physical planning. It adresses national concerns by searchng for solutions at city level. For that purpose, it focuses on three key areas:spatial or regional harmnony, which examines the main drivers of urban growth in the developing world and explores and explores the spatial nuances of economic and social policies; social harmony, which presents and analyses new data on urban inequalities worldwide and describes the types of shelter deprivations experienced by slum dwellers in developing world regions; and environmental harmony, which examines the role of cities in the Climate change debate, and the impact of global warming on the most vulnerable cities
Includes Bibliography
Keywords: Cities